2016
DOI: 10.1039/c6dt03497g
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the chemical reaction equilibria of element 104, rutherfordium: solid–liquid extraction of Rf, Zr, Hf and Th with Aliquat 336 resin from HCl

Abstract: We successfully observed the equilibrium state of the chemical reactions for superheavy elements on a one-atom-at-a-time scale; we investigated the time dependence of the extraction behaviour of element 104, Rf. The distribution coefficient of Rf in 9 M HCl was found to be higher than those of its homologous elements, probably due to differences in the chloride complexation of Rf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Chloride complexation of Zr, Hf, and Rf using a solid–liquid extraction technique with Aliquat 336 resin (anion exchanger) in HCl at equilibrium was performed by Yokokita et al 59 ) They reported a similar result to that shown in Fig. 7 (a).…”
Section: Complex Formation Studies Of Rf and Dbmentioning
confidence: 69%
“…Chloride complexation of Zr, Hf, and Rf using a solid–liquid extraction technique with Aliquat 336 resin (anion exchanger) in HCl at equilibrium was performed by Yokokita et al 59 ) They reported a similar result to that shown in Fig. 7 (a).…”
Section: Complex Formation Studies Of Rf and Dbmentioning
confidence: 69%
“…This methodology also has a possibility of the first observation of the equilibrium of the chemical reactions for SHE. 33 In coprecipitation study, the coprecipitation method was proposed to investigate the hydroxide and ammine complexation of SHEs as a quite new method for SHE chemistry. In addition, good energy resolution in alpha spectroscopy was confirmed for precipitated samples.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, solid-liquid extraction experiment of 261 Rf with AMBER at RIKEN was recently achieved and interesting results were reported. 33…”
Section: Online Solid-liquid Extraction For Zr and Hfmentioning
confidence: 99%